Tour / Travel Business Planning Strategies In The New Normal Era - Muhammad Reynaldi Aulia; Evi Novianti; yustikasari yustikasari (Jurnal Ilmiah Manajemen dan Bisnis, 2022)
The emergence of the COVID-19 pandemic gave rise to a new social lifestyle, which was then called the era of new-normal. This change has an impact on the tourism business sector, especially the travel/tour business due to changes in consumer behavior trends. This journal aims to know how the travel/tour business planning strategy is good in the new normal era by using the library research method. The results of this study are a good travel/tour business planning strategy in the new normal era where the preparation emphasizes technology adaptation, cleanliness, security, and the uniqueness of the products and services offered.